PENGARUH KOMPETENSI TERHADAP KINERJA KERJA PEGAWAI DI UPT. PERPUSTAKAAN UNIVERSITAS TADULAKO - Mokodompit, Ulfiyah. T. (Katalogis, 2017)
The purpose of this study was to determine the effects of competence on employees working performance at the technical implementation units (TIUs) of Tadulako University, consisting of Motive (X1), Personality (X2), Self-Concept (X3), Knowledge (X4), and Skill (X5) on Performance (Y). This study used multiple linear regression analysis with saturation sampling technique. The respondents in this study were amounting to 37 people. Through partial test, it was found that the Motive (X1), Personality (X2), Self-Concept (X3), Knowledge (X4), and Skill (X5) variables had significant influences on employees working performance in the TIUs of Tadulako University. Simultaneous test results show that the regression coefficients of the Motive (X1) and Personality (X2) independent variables had negative signs, meaning that any enhancement of the Motive and Personality values would not boost employees working performance; while the regression coefficients of the Self-Concept (X3), Knowledge (X4) and Skill (X5) independent variables had positive signs, meaning that any enhancement of the Self-Concept, Knowledge, and Skill values would boost employees working performance; the effeck of simultaneously competence on the performance of employees working in UPT. Tadulako university libraries at 0,678. The magnitude of the partial competence to competence in general are at 0,537 that influence is strong enogh.